2017
DOI: 10.1016/j.bcp.2017.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of microRNAs directly regulating the UDP-glucuronosyltransferase 1A subfamily enzymes by a functional genomics approach

Abstract: Posttranscriptional repression of UDP-glucuronosyltransferase (UGT) 1A expression by microRNAs (miRNAs) may be an important mechanism underlying interindividual variability in drug glucuronidation. Furthermore, the UGT1A 3’-UTR shared by all UGT1A enzymes is polymorphic, containing three linked SNPs (rs10929303, rs1042640, and rs8330) that could influence miRNA binding. The aim of this study was to identify the complete complement of miRNAs that could regulate UGT1A expression through binding to the reference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…Previous results from our laboratory demonstrated that miR-103b and miR-376b-3p have functional MREs in the common UGT1A 3’-UTR [17]. In the current work we showed that miR-103b and miR-376b-3p were also among the miRNAs with functional MREs in the UGT2B15 3’-UTR.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Previous results from our laboratory demonstrated that miR-103b and miR-376b-3p have functional MREs in the common UGT1A 3’-UTR [17]. In the current work we showed that miR-103b and miR-376b-3p were also among the miRNAs with functional MREs in the UGT2B15 3’-UTR.…”
Section: Discussionsupporting
confidence: 67%
“…In recent work we used the same in vitro system to perform a genome-wide screen of the miRNA mimic library with the pMIR-REPORT luciferase vector carrying the reference UGT1A 3’-UTR or the variant 3’-UTR [17]. This way we demonstrated that SNP rs10929303 C>T located in the common UGT1A 3’-UTR created a novel MRE for miR-21–3p.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A plasmid constitutively expressing renilla luciferase was cotransfected as an internal control to correct for differences in both transfection and harvesting efficiencies [12]. The transfections were performed in duplicate, and at least three independent experiments were performed [13].…”
Section: Luciferase Reporter Assaymentioning
confidence: 99%